2017
DOI: 10.1007/s00253-017-8380-8
|View full text |Cite
|
Sign up to set email alerts
|

Microbial transformations of selenite by methane-oxidizing bacteria

Abstract: Methane-oxidizing bacteria are well known for their role in the global methane cycle and their potential for microbial transformation of wide range of hydrocarbon and chlorinated hydrocarbon pollution. Recently, it has also emerged that methane-oxidizing bacteria interact with inorganic pollutants in the environment. Here, we report what we believe to be the first study of the interaction of pure strains of methane-oxidizing bacteria with selenite. Results indicate that the commonly used laboratory model strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 45 publications
4
56
0
Order By: Relevance
“…The Debye-Waller factor (σ 2 ) of this shell, ranging from 0.0030 to 0.0045 Å 2 in all samples, decrease with reaction time, suggesting an increase of structural order with time (see Table 1). This could explain, as reported by Eswayah et al, 17 the biotransformation of amorphous SeNPs (24 h) to trigonal Se nanostructures (72 h and 144 h). Attempts to fit the second Se-Se coordination shell at about 3.63-3.70 ± 0.02 Å failed due to the small amplitude of this peak in the 3 studied samples.…”
Section: Microscopic Characterization Of the Purified Selenium Nanopasupporting
confidence: 71%
See 3 more Smart Citations
“…The Debye-Waller factor (σ 2 ) of this shell, ranging from 0.0030 to 0.0045 Å 2 in all samples, decrease with reaction time, suggesting an increase of structural order with time (see Table 1). This could explain, as reported by Eswayah et al, 17 the biotransformation of amorphous SeNPs (24 h) to trigonal Se nanostructures (72 h and 144 h). Attempts to fit the second Se-Se coordination shell at about 3.63-3.70 ± 0.02 Å failed due to the small amplitude of this peak in the 3 studied samples.…”
Section: Microscopic Characterization Of the Purified Selenium Nanopasupporting
confidence: 71%
“…Attempts to fit the second Se-Se coordination shell at about 3.63-3.70 ± 0.02 Å failed due to the small amplitude of this peak in the 3 studied samples. The bond distance of this shell would give insights on the crystalline Se, as was indicated by Eswayah et al 17 and Scheinost and Charlet. 42 Thus, due to the fact that EXAFS is a bulk technique, no strong structural evidence on the transformation of amorphous Se to trigonal Se was demonstrated, as it was suggested by STEM/HAADF analysis.…”
Section: Microscopic Characterization Of the Purified Selenium Nanopamentioning
confidence: 74%
See 2 more Smart Citations
“…13 Several studies have previously reported that bacteria can produce intracellular and extracellular amorphous Se (a-Se) nanospheres with a size ranging from 100 to 200 nm. 14,21 To a lesser extent, few studies have also described the formation of biogenic trigonal and monoclinic selenium (t-Se and m-Se). 8,22 Ho et al 23 reported the control of organic solvents like DMSO in the transformation of biogenic a-Se nanospheres to 1D t-Se nanostructures (e.g.…”
Section: Introductionmentioning
confidence: 99%